Botanical Bosom Serpent Traditions. Issue 3 (2nd July 2020) - Ermacora, Davide
Abstract: This article surveys examples of 'botanical bosom serpents'; that is, stories where a plant, or some vegetable element, is said to enter and/or grow in the human body. These can be found in sources—for the most part European—from ancient times onwards. This is a preliminary study, as the topic is one that has been neglected by folklorists and historians of medicine.